The Impact of Financial Literacy and Digital Transformation on MSME Performance in Bandung City - Dwi Rahmawati; Destiana Destiana; Jufri Yandes (BASKARA : Journal of Business and Entrepreneurship, 2025)
Micro, small, and medium-sized enterprises (MSMEs) play an influential part in the economy of Indonesia. Their contribution to economic development is often hindered by insufficient financial literacy and a slow adoption of digital transformation. Enhancing these areas is crucial for boosting competitiveness, resilience, and sustainable growth. This research examines the impact of financial literacy, financial attitudes, financial satisfaction, and digital transformation on the performance of MSMEs in Bandung City. A quantitative research approach was utilized, employing primary data gathered through structured questionnaires given to MSME proprietors. The data analysis was completed using the partial least squares (PLS) technique, with the measurement model evaluated through convergent validity, discriminant validity, and reliability tests to maintain methodological rigor. The findings demonstrate that financial literacy, financial attitudes, financial satisfaction, and digital transformation each have a partial yet significant impact on MSME performance. The findings underscore the importance of integrating financial capability development with strategies for digital adoption to enhance business performance. The uniqueness of this research lies in its integration of financial behaviors and digital transformation aspects, providing a more comprehensive understanding of the factors influencing MSME performance. This study presents practical recommendations for policymakers and business leaders in developing strategies that enhance MSME competitiveness in the digital economy